Neural basis of recollection in first‐episode major depression. Issue 2 (3rd January 2012) - van Eijndhoven, Philip; van Wingen, Guido; Fernández, Guillén; Rijpkema, Mark; Pop‐Purceleanu, Monica; Verkes, Robbert Jan; Buitelaar, Jan; Tendolkar, Indira
Abstract Background. Patients with major depressive disorder (MDD) display impairments in recollection, which have been explained by both hippocampal and prefrontal dysfunction. Here, we used an event‐related fMRI design, to dissociate hippocampal and prefrontal contributions to the neural processes involved in recollection success and recollection attempt early in the course of MDD. Methods. To disentangle state‐ and trait‐effects of depression, we included 20 medication‐naive patients with a first depressive episode, 20 medication‐free patients recovered from a first episode, and 20 matched, healthy controls in an event‐related fMRI study using a source recollection paradigm. Results. Group comparisons revealed that during the acute state of depression there is an increase in left prefrontal activity related to recollection attempt, while there were no differences in neural correlates of successful recollection. Conclusions. Our results indicate that in the early course of depression, depressive state is associated with increased left prefrontal activation during the attempt to recollect source information suggesting an increased need for executive control during recollection in MDD. In this sample of first‐episode MDD patients we found no evidence for hippocampal dysfunction. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.